Low-fat dietary pattern and cardiovascular disease: results from the Women’s Health Initiative randomized controlled trial - Prentice, Ross L (Am J Clin Nutr, 2017)
Background: The influence of a low-fat dietary pattern on the cardiovascular health of postmenopausal women continues to be of public health interest. Objective: This report evaluates low-fat dietary pattern influences on cardiovascular disease (CVD) incidence and mortality during the intervention and postintervention phases of the Women’s Health Initiative Dietary Modification Trial. Design: Participants comprised 48,835 postmenopausal women aged 50–79 y; 40% were randomly assigned to a low-fat dietary pattern intervention (target of 20% of energy from fat), and 60% were randomly assigned to a usual diet comparison group. The 8.3-y intervention period ended in March 2005, after which >80% of surviving participants consented to additional active follow-up through September 2010; all participants were followed for mortality through 2013. Breast and colorectal cancer were the primary trial outcomes, and coronary heart disease (CHD) and overall CVD were additional designated outcomes. Results: Incidence rates for CHD and total CVD did not differ between the intervention and comparison groups in either the intervention or postintervention period. However, CHD HRs comparing these groups varied strongly with baseline CVD and hypertension status. Participants without prior CVD had an intervention period CHD HR of 0.70 (95% CI: 0.56, 0.87) or 1.04 (95% CI: 0.90, 1.19) if they were normotensive or hypertensive, respectively (P-interaction = 0.003). The CHD benefit among healthy normotensive women was partially offset by an increase in ischemic stroke risk. Corresponding HRs in the postintervention period were close to null. Participants with CVD at baseline (3.4%) had CHD HRs of 1.47 (95% CI: 1.12, 1.93) and 1.61 (95% CI: 1.02, 2.55) in the intervention and postintervention periods, respectively. However, various lines of evidence suggest that results in women with CVD or hypertension at baseline are confounded by postrandomization use of cholesterol-lowering medications. Conclusions: CVD risk in postmenopausal women appears to be sensitive to a change to a low-fat dietary pattern and, among healthy women, includes both CHD benefit and stroke risk. This trial was registered at clinicaltrials.gov as NCT00000611.